Traffic conformance issues in passive optical networks: challenges and solutions. (6th January 2009) - Ngo, M. Thanh; Gravey, Annie
Broadband passive optical networks (PONs) share a single optical fiber transmission system between several customers. A dynamic bandwidth allocation (DBA) is used to avoid collisions for upstream traffic. An ideal DBA should support both committed bandwidth and best effort services while efficiently utilising the available bandwidth and providing isolation between customers in order to offer fair access to resources. In the present paper, we assume that each customer negotiates traffic profiles for its upstream committed bandwidth traffic. We show that a DBA that does not take into account conformance to the negotiated traffic profiles cannot isolate compliant customers from non-compliant customers, leading to QoS degradations for compliant customers. We then propose a framework for taking into account the traffic conformance within the DBA. This study is illustrated by an original, priority based DBA designed for Ethernet optical networks (EPONs).